Agri-Tech Supply Chain Business Opportunities & Challenges in Rural (Hill Area) India - Talachutla, Santosh Kumar (Digital Repository of Theses - SSBM Geneva, 2024)
Agricultural technology (Agri-Tech) is poised to revolutionize the agricultural landscape of India's rural hill regions, where traditional farming practices are predominantly prevalent. This thesis explores the multifaceted opportunities and challenges that emerge from integrating Agri-Tech into the supply chains in these areas, aiming to provide a comprehensive understanding of its potential impact on local agriculture and economic development. The study begins by contextualizing the unique environmental, economic, and social dynamics of rural hill areas in India, which are characterized by rugged terrains, limited accessibility, and a lack of infrastructural development. These factors traditionally hinder agricultural productivity and market access, presenting a compelling case for the adoption of technology-driven solutions. Opportunities for Agri-Tech in these regions are vast and varied. One of the significant opportunities identified is the application of precision agriculture technologies, which can lead to optimized input usage such as water, fertilizers, and pesticides, thus enhancing crop yields and sustainability. Moreover, the adoption of digital platforms can play a pivotal role in overcoming information asymmetries by providing farmers with real-time data on weather, soil health, and market prices. Another critical opportunity lies in the use of blockchain and IoT-based technologies to improve supply chain transparency and traceability, reducing losses and ensuring fair compensation to farmers.